2014
DOI: 10.1097/01.anes.0000435741.97234.04
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Potency of Different Propofol Formulations

Abstract: Plain propofol formulations are not equipotent, but comparable doses were required when lidocaine was concomitantly administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A multicenter double blinded trial compared the dose of propofol for induction (using a closed loop infusion guided by Bispectral Index (BIS)) and patient discomfort with and without lidocaine and found that the different formulations were not equipotent - Propoven ® required a higher dose for induction (2.2 ± 0.1 mg/kg) than Diprivan ® (1.8 ± 0.1 mg/kg) or Lipuro ® (1.7 ± 0.1 mg/kg; P = 0.02); however, induction doses were similar when propofol formulations were mixed with lidocaine [18]. …”
Section: ) Commercially Available Formulationsmentioning
confidence: 99%
“…A multicenter double blinded trial compared the dose of propofol for induction (using a closed loop infusion guided by Bispectral Index (BIS)) and patient discomfort with and without lidocaine and found that the different formulations were not equipotent - Propoven ® required a higher dose for induction (2.2 ± 0.1 mg/kg) than Diprivan ® (1.8 ± 0.1 mg/kg) or Lipuro ® (1.7 ± 0.1 mg/kg; P = 0.02); however, induction doses were similar when propofol formulations were mixed with lidocaine [18]. …”
Section: ) Commercially Available Formulationsmentioning
confidence: 99%
“…Finally, propofol was used without lidocaine, although lidocaine can reduce pain during injection. [13] Hypothetically, the lack of an observed effect might have been due to a loss of focus and hypnotic state during this painful stimulus and before induction, thus “resetting” the patient, as suggested by the reactions observed during injection in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a previous study on the potency of various propofol formulations, [13] the mean propofol dose required to obtain anesthesia induction (BIS < 60 for at least 30 seconds) was 2.2 mg/kg (standard deviation 0.6). Considering a statistical power of 90% and an alpha risk of 5% to detect a dose reduction of 25%, the number of patients needed in each group was 40.…”
Section: Methodsmentioning
confidence: 99%
“…The use of lidocaine to reduce propofol injection pain can lead to adverse effects, such as cardiovascular and hemodynamic influence and swelling at the intravenous access site, and can cause confusion regarding the required propofol dose for induction (Ahmad et al, 2013;Kim et al, 2011;Le Guen et al, 2014). Few studies have compared propofol injection pain between lidocaine administration and local warming.…”
Section: Introductionmentioning
confidence: 99%